A case of dysarthria - BN, Pranesha Rao (Journal of All India Institute of Speech and Hearing, 1970)
Mr S., aged 33 years reported to the clinic on 7-3-1967 with a complaint of misarticulation from childhood. The case felt that the tonsils operation that he underwent at the age of 5 might have caused the problem. Mothertongue of the case is Tamil and he knows English, Hindi and Sanskrit. He is a graduate. He has six siblings and there was no family history of speech or hearing defects or any other illnesses. No significant prenatal history except instrumental delivery. Other milestones of development were reported to be normal. The case underwent tonsils operation at the age of 5 and tongue tie operation at the age of 7. Otolaryngological examinations revealed scarring and contraction of soft palate, scarring and retraction of tonsils, and chronic lymphoid hyperplasia of pharynx with no unusual infection of upper respiratory tract. Neurological examinations revealed normal reflexes. No abnormalities were noted with regard to the functions of higher centers and cranial nerves except for a slight paresis of orbicularis oris and pharyngeal muscles. Hemiatrophy of the tongue on right side was also noticed. It was diagnosed as residual traumatic birth injury. There was no hearing loss and psychological examinations revealed no specific problems relevent to the defect